The Implementation of TEYL in Indonesia Revisited: A Study at Primary Schools in Bandung - Slamet Suwanto; Fadhlur Rahman (International Journal of Education, Language, and Religion, 2022)
This study explored Teaching English to Young Learners (TEYL) implementation in elementary schools in Bandung, Indonesia. Surveys, interviews, observation, and document analysis were used to obtain data. The survey was distributed to 30 TEYL teachers from 30 schools within the region. Interviews were conducted with four teachers from four different schools. The data were triangulated and descriptively examined to assess TEYL in primary schools. The findings showed a mismatch between the government's policy on English instruction in primary schools and TEYL's implementation. In the 30 schools investigated, English was taught as local content in 21 schools (70%) and extracurricular in 7 schools (23%). Meanwhile, only 2 schools (7%) did not conduct English in their teaching-learning process. Due to the lack of government supervision, teachers are free to construct their own TEYL course content. According to the interviews, adopting TEYL is challenging due to varying teacher abilities and the availability of school’s infrastructure. The discussion suggests some recommendations on how to utilize the TEYL curriculum in Indonesian's primary schools effectively.